Amorphous Silicon Single-Junction Thin-Film Solar Cell Exceeding 10% Efficiency by Design Optimization. (4th November 2012) - Kabir, Mohammed Ikbal; Shahahmadi, Seyed A.; Lim, Victor; Zaidi, Saleem; Sopian, Kamaruzzaman; Amin, Nowshad
Abstract : The conversion efficiency of a solar cell can substantially be increased by improved material properties and associated designs. At first, this study has adopted AMPS-1D (analysis of microelectronic and photonic structures) simulation technique to design and optimize the cell parameters prior to fabrication, where the optimum design parameters can be validated. Solar cells of single junction based on hydrogenated amorphous silicon (a-Si:H) have been analyzed by using AMPS-1D simulator. The investigation has been made based on important model parameters such as thickness, doping concentrations, bandgap, and operating temperature and so forth. The efficiency of single junction a-Si:H can be achieved as high as over 19% after parametric optimization in the simulation, which might seem unrealistic with presently available technologies. Therefore, the numerically designed and optimized a-SiC:H/a-SiC:H-buffer/a-Si:H/a-Si:H solar cells have been fabricated by using PECVD (plasma-enhanced chemical vapor deposition), where the best initial conversion efficiency of 10.02% has been achieved (V o c = 0.88  V, J sc = 15.57  mA/cm 2 andFF =    0.73 ) for a small area cell (0.086 cm 2 ). The quantum efficiency (QE) characteristic shows the cell's better spectral response in the wavelength range of 400 nm–650 nm, which proves it to be a potential candidate as the middle cell in a-Si-based multijunction structures.